Varieties of male-sexual-identity development in clinical practice: a neuropsychoanalytic model - Stortelder, Frans (Frontiers in Psychology, 2014)
Variations of sexual-identity development are present in all cultures, as well as in many animal species. Freud, founding father of psychoanalysis, believed that all men have an inherited, bisexual disposition, and that many varieties of love and desire are experienced as alternative pathways to intimacy. In the neuropsychoanalytic model, psychic development starts with the constitutional self. The constitutional self is comprised of the neurobiological factors which contribute to sexual-identity development. These neurobiological factors are focused on biphasic sexual organization in the prenatal phase, based on variations in genes, sex hormones, and brain circuits. This psychosocial construction of sexual identity is determined through contingent mirroring by the parents and peers of the constitutional self. The development of the self—or personal identity—is linked with the development of sexual identity, gender-role identity, and procreative identity. Incongruent mirroring of the constitutional self causes alienation in the development of the self. Such alienation can be treated within the psychoanalytic relationship. This article presents a contemporary, neuropsychoanalytic, developmental theory of male-sexual identity relating to varieties in male-sexual-identity development, with implications for psychoanalytic treatment, and is illustrated with three vugnettes from clinical practice.